Lung Transplantation in a Patient with Fibrosing Alveolitis. Issue 5771 (14th August 1971) - Hugh-Jones, P.; Macarthur, A. M.; Cullum, P. A.; Mason, S. A.; Crosbie, W. A.; Hutchison, D. C. S.; Winterton, M. C.; Smith, A. P.; Mason, B.; Smith, L. A.
Abstract : The transplantation of the right lung into a man aged 40 who was suffering from cryptogenic fibrosing alveolitis is described. Before transplantation he had been dependent on oxygen, even at rest, for 24 hours a day for almost two years. The donor was a boy of 16 years who had had a fatal cerebral haemorrhage. The transplanted lung functioned perfectly from the time of operation until the patient's sudden death two months later from an overwhelming haemoptysis apparently from a small peribronchial abscess rupturing into the pulmonary artery. By the third postoperative week the patient had been able to walk unaided and without distress outdoors. The problem of differentiating infection from incipient rejection is discussed. We conclude that clinically successful lung transplantation can be achieved, but only if the problems of lung function, infection, and immunosuppression can all be overcome.